Diversity and functions of volatile organic compounds produced by Streptomyces from a disease-suppressive soil - Cordovez, Viviane; Carrión, Victor J.; Etalo, Desalegn W; Mumm, Roland; van Wezel, Gilles P; Raaijmakers, Jos M. (Frontiers, 2015)
In disease-suppressive soils, plants are protected from infections by specific root pathogens due to the antagonistic activities of soil and rhizosphere microorganisms. For most disease-suppressive soils, however, the microorganisms and mechanisms involved in pathogen control are largely unknown. Our recent studies identified Actinobacteria as the most dynamic phylum in a soil suppressive to the fungal root pathogen Rhizoctonia solani. Here we isolated and characterized 300 isolates of rhizospheric Actinobacteria from the Rhizoctonia-suppressive soil. Streptomyces species were the most abundant, representing approximately 70% of the isolates. Streptomyces are renowned for the production of an exceptionally large number of secondary metabolites, including volatile organic compounds (VOCs). VOC profiling of 12 representative Streptomyces isolates by SPME-GC-MS allowed a more refined phylogenetic delineation of the Streptomyces isolates than the sequencing of 16S rRNA and the house-keeping genes atpD and recA only. VOCs of several Streptomyces isolates inhibited hyphal growth of R. solani and significantly enhanced plant shoot and root biomass. Coupling of Streptomyces VOC profiles with their effects on fungal growth, pointed to VOCs potentially involved in antifungal activity. Subsequent assays with five synthetic analogs of the identified VOCs showed that methyl 2-methylpentanoate, 1,3,5-trichloro-2-methoxy benzene and the VOCs mixture have antifungal activity. In conclusion, our results point to a potential role of VOC-producing Streptomyces in disease suppressive soils and show that VOC profiling of rhizospheric Streptomyces can be used as a complementary identification tool to construct strain-specific metabolic signatures.
Keywords: Suelos sin agentes patógenos; Actinobacteria; SPME-GC-MS; antifungal activity; plant growth promotion; suppressive soil